Pemerintah Hamas dan Prospek Perdamaian - Wardoyo, Broto (Global: Jurnal Politik Internasional, 2006)
The assumption of Hamas as a terrorist organization has led the peace process to adopt the strategy to exclude Hamas. Hamas’ victory in the 2006 parliament election soon followed by resistances and rejections from Israel, the U.S. and several European countries. This eventually leads to the isolation of Palestine by donor countries and affects Palestinian economy. In order to start the peace process, the world first needs to acknowledge the Hamas government and not to assume them as a terrorist organization. The peace process should realize that Hamas’ acts during the 1993-2005 periods were their attempts to enter Palestinian political structure. Hamas show a more pragmatic political move lately with their readiness to enter the negotiation as long as Israel will retreat from the Occupied Territories. This shows their commitment to peace process rather than to ideological values of jihad to free the whole land of Palestine and erect an Islamic State. Hamas’ commitment to hudna should be seen as their attempt to create a peace mechanism. This attempt should be followed by a negotiation between Israel and the Palestinian Authority (PA) and their guidance of a fair mediator.